Fatal Foreign Body Aspirations in Children - Gören, Süleyman; Gürkan, Fuat; Tıraşçı, Yaşar; Kaya, Ziya (The Bulletin of Legal Medicine, 2003)
As a very serious reason of accidental deaths in childhood, we have aimed to investigate deaths due to foreign body aspiration (FBA), since its incidence has not decreased despite advances in the techniques and instruments for its emergency treatment. We retrospectively reviewed the records of forensic cases due to FBA examined at the Diyarbakır Branch of the Council of Forensic Medicine between 1990 and 2003. Over this period this office investigated 8330 medicolegal deaths cases, 22 of which were children under 15 years of age due to FBA. Of the victims, 14 (63.6%) were male and 8 (36.4%) were females. The mean age of the victims was 2.2+0.6 years. There were 20 (90.9 %) children between 1 and 3 years, and two other cases at 2/12 and 5 years of ages. All fatal aspirations occurred at home. Food was the most commonly aspirated foreign body in 81.8% of the cases, nuts being the most common in 50%. Carina (54.5%) was the most common site of the foreign body in the respiratory tract. In conclusion, food asphyxiation remains a common problem particularly in children between 1 and 3 years of age in our region. These fatal accidents could be prevented by parent education and early recognition and management of the situation.Key words: Foreign body, aspiration, child, death
Keywords: foreign body; aspiration; child; death